An assessment of the relationship between national rates of Covid‐19 incidence and mortality as reported to an international comparison database: An ecological study - Azad Shokri; Hassan Mahmoodi; Bakhtiar Piroozi; Yousef Moradi; Farhad Moradpour; Ghobad Moradi; Ali Ebrazeh; Parisa Daftarifard (Health Science Reports, 2023)
Abstract Background and Aims Making a judgment only based on formal national reports can be misleading. We aimed to assess the relationship between countries' development indicators and reported coronavirus disease 2019 (Covid‐19)‐related incidences and death. Methods Covid‐19 related incidence and death cases were extracted from the updated Humanitarian Data Exchange Website on October 8, 2021. Univariable and multivariable negative binomial regression were utilized to investigate the relationship between development indicator and incidence and mortality from Covid‐19 by calculating the Incidence rate ratio (IRR), mortality rate ratio (MRR), and fatality risk ratio (FRR). Results Very high human development index (HDI) compared with low HDI (IRR:3.56; MRR:9.04), the proportion of physicians (IRR:1.20; MRR:1.16), besides extreme poverty (IRR:1.01; MRR:1.01) were independently correlated with the mortality and incidence rate of Covid‐19. Very high HDI and population density were inversely correlated with the fatality risk (FRRs of 0.54 and 0.99). The cross‐continental comparison shows Europe and the North Americas, had significantly higher incidence and mortality rates with IRR of 3.56 and 1.84 as well as MRRs of 6.65 and 3.62, respectively. Also, they inversely correlated with the fatality (FRR:0.84 and 0.91, respectively). Conclusion A positive correlation between the fatality rate ratio based on countries' development indicators and the reverse for the incidence and mortality rate was found. Developed countries with sensitive healthcare systems can diagnose infected cases as soon as possible. Also, the mortality rate of Covid‐19 will be accurately registered and reported. Due to more access to diagnostic tests, patients are diagnosed at the initial stages and will have a better opportunity to receive treatment. This leads to higher reports of incidence/and/or mortality rates and lower fatality of COVID‐19. In conclusion, more Covid‐19 incidence and mortality cases in developed countries can result from a more comprehensive care system and a more accurate recording procedure.